Spatiotemporal Coupling Characteristics and Interactive Effects of Government Environmental Governance, Green Finance, and Carbon Emission Performance in the Yangtze River Delta Urban Agglomeration - Qi Sun; Changjun Jiang; Xinyue Zheng (SAGE Open)
There is a consensus among scholars that low-carbon development has become the means to achieve sustainable development in China. The Yangtze River Delta urban agglomeration (YRDUA) undoubtedly plays a key role in advancing this goal. This study brings government environmental governance (GEG), green finance (GF), and carbon emission performance (CEP) into a unified theoretical framework. The research object is comprised of 26 cities in the YRDUA, from 2010 to 2021. In addition, a coupling coordination model, Dagum Gini coefficient decomposition method, and a panel vector autoregression (PVAR) model are used for in-depth analysis. The results indicate: (1) the coupling coordination degree (CCD) of GEG, GF, and CEP has experienced a leap-forward promotion of “primary coordination→modern coordination.” However, high-quality coordinated development is far from being realized, and the whole is in the primary coordination stage. (2) The spatial differences of CCD are obvious, showing an overall pattern of “multi-core” radiation and an interregional pattern of “high in the east and low in the west.” (3) Finally, GEG, GF, and CEP show a strong trend of development according to their own inertia and self-strengthening characteristics; the interaction among them is also gradually becoming stable. Based on the research findings, this study offers targeted recommendations to promote sustainable development in the YRD further.